2021
DOI: 10.1063/5.0048042
|View full text |Cite
|
Sign up to set email alerts
|

Negligible spin–charge conversion in Bi films and Bi/Ag(Cu) bilayers

Abstract: Spin pumping experiments using ferromagnetic metals have reported highly efficient spin–charge conversion in Bi and at the Bi/Ag interface, possibly due to the inverse Rashba–Edelstein effect. However, longitudinal spin Seebeck effect experiments using the yttrium iron garnet ferrimagnetic insulator in Bi films and Bi/Ag bilayers do not show evidence of appreciable spin-to-charge conversion except the large Nernst signal inherent to Bi. These contrasting conclusions highlight the differences between magnetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…[1,2] In principle, if the transverse spin-polarized electrons are fully deflected to the longitudinal direction, the spin Hall angle becomes 1. [3] However, a novel mechanism, called the inverse Edelstein effect, in topological materials (e.g., Bi 2 Se 3 , (BiSb) 2 Te 3 , and Bi 1−x Se x ) makes it possible to overcome this limit effectively (𝛾 > 1). [4][5][6][7][8] Recently, a giant spin Hall angle of 52 has been reported for Bi 0.9 Sb 0.1 alloy, [9] and a theoretical study demonstrated that the spin Hall angle can be tuned depending on the Sb concentration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1,2] In principle, if the transverse spin-polarized electrons are fully deflected to the longitudinal direction, the spin Hall angle becomes 1. [3] However, a novel mechanism, called the inverse Edelstein effect, in topological materials (e.g., Bi 2 Se 3 , (BiSb) 2 Te 3 , and Bi 1−x Se x ) makes it possible to overcome this limit effectively (𝛾 > 1). [4][5][6][7][8] Recently, a giant spin Hall angle of 52 has been reported for Bi 0.9 Sb 0.1 alloy, [9] and a theoretical study demonstrated that the spin Hall angle can be tuned depending on the Sb concentration.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 , 2 ] In principle, if the transverse spin‐polarized electrons are fully deflected to the longitudinal direction, the spin Hall angle becomes 1. [ 3 ] However, a novel mechanism, called the inverse Edelstein effect, in topological materials (e.g., Bi 2 Se 3 , (BiSb) 2 Te 3 , and Bi 1− x Se x ) makes it possible to overcome this limit effectively ( γ > 1). [ 4 8 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the magnitude of the reported Θ sH values varies from zero (negligibly small) to 24 %, depending on the spin current detection method and also the magnetic material used to inject spin current in the experiments [33]. Moreover, the signs of the reported Θ sH values could also differ.…”
Section: Introductionmentioning
confidence: 99%
“…Since bismuth is a semimetal with the electrical conductivity being much lower than that of platinum [20], one would expect bismuth to have a very large spin Hall angle (Θ sH ) (the ratio of the spin current to the longitudinal charge current, i.e., charge-spin conversion efficiency). Therefore, many investigations on spin current phenomena in Bi semimetal systems have been carried [29][30][31][32][33][34] and indeed large spin Hall angles of about 10 % have been reported in some of these experiments [29].…”
Section: Introductionmentioning
confidence: 99%